Ankle Fractures Treated With Locked Fibular Intramedullary Nailing: Description and Outcomes of a Minimally Invasive Open Technique - Ricketts, Cassandra; Sajid, Mir Ibrahim; McCaskey, Meghan; Andrews, Reed; Mir, Hassan R (Journal of orthopaedic trauma, 2025)
To describe and report outcomes of a minimally invasive open fibular intramedullary (IM) nailing technique for fixation of ankle fractures. Case Series. Urban Level 1 trauma center. Adult patients with ankle fractures (OTA 44A-C) treated with locked fibular IM nailing through a minimally invasive open technique for fracture and syndesmotic reduction between 2021 and 2024. Quality of reduction, complications, and patient-reported outcomes. A total of 150 consecutive patients operated by a single surgeon were included. Mean age was 53.3 (17-97) years, and mean body mass index was 30.6 ± 7.4 kg/m 2 . Ninety-three (62%) patients were female, and 78 (52%) patients were White. Seventy-two (48%) patients were obese, 40 (27.7%) patients were current/former smokers, 39 (26%) patients had diabetes, and 23 (15.3%) patients had open fractures. Thirty-seven (24.7%) patients had isolated lateral malleolus fractures, 48 (32%) had bimalleolar fractures, and 65 (43.3%) had trimalleolar fractures. One hundred and twenty-three (82%) patients had 2 syndesmotic screws placed, 26 patients (17.3%) had 1 screw, and 1 patient (0.7%) had none. Quality of reduction was good for 98%, fair for 2%, and poor for none per McLennan criteria. One hundred thirteen patients (75.3%) were followed until clinical and radiographic union for a mean of 7.6 months (range 3-22) months. One hundred and ten patients (97.3%) went on to successful clinical and radiographic union after the index procedure. No patient had a superficial surgical-site infection, and 3 (2.6%) had deep surgical-site infections. Three patients had a loss of reduction, and 6 patients had implant failure (5 broken syndesmotic screws, and 1 medial malleolus screw). Nine (8%) patients had unplanned reoperations (3 for debridement, 2 for loss of reduction, and 4 for removal of symptomatic implants). Mean ankle range of motion at final follow-up visit was 12.9 degrees (0-40) of dorsiflexion, 39.6 degrees (10-70) of plantar flexion, 23.5 degrees (5-40) of inversion, and 18.2 degrees (5-50) of eversion. Mean PROs at final follow-up visit were Global Physical Health: 42.4 (23.5-67.6), Global Mental Health: 47.5 (21-67.6), Physical Function: 37.5 (14.7-57.8), Pain: 54.9 (22-72), and Mobility: 36.9 (16-65.3). Minimally invasive open fibular IM nailing allowed for excellent reduction and results in union with low rates of complications and good patient-reported outcomes. Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.